CIVIC EDUCATION AS AN INSTRUMENT OF STRENGTHENING STUDENTS’ ARCHIPELAGO INSIGHT - Sulkipani Sulkipani; Vina Amilia Suganda M; Edwin Nurdiansyah (Sriwijaya University Learning and Education International Conference, 2018)
This literature review aims to analyze the nature of civic education as an instrument of strengthening student insight. That the love of citizens of his country will grow when the citizens have strong knowledge or insight about the nation and country. In the context of Indonesia, the Insight to the nation and state is called the insight of the archipelago. The insight of the archipelago is defined as the perspective of the Indonesian nation and state against itself and its environment. The concept of self means the Indonesian nation, and the environment refers to the State of Indonesia in the sense of the territory of the of the Indonesia Republic. The insight of the archipelago becomes the visional foundation of Indonesia to make all citizens must have strong insight into the archipelago. Efforts to strengthen the insight of the archipelago must be continuously done in order to maintain the unity and existence of the Indonesia Republic. Strategic efforts that can be taken include through civic education in college. Civic education in universities specifically examines the nature and implementation of the insight of the archipelago in the life of the nation and state.